Digital Transformation: Exploring the Relationship Between Literacy, Motivation, and TPACK in Elementary Education - Frisco Harmadi; Ika Maryani; Sukirman Sukirman; Elsa Carmen N Montano (Universitas Muhammadiyah Surakarta, 2025)
The rapid advancement of technology in education has not been fully aligned with elementary school teachers’ ability to integrate it into their teaching practices. This gap persists due to the limited development of Technological Pedagogical Content Knowledge (TPACK) and the lack of research examining the combined influence of digital literacy and teacher motivation on TPACK. This study aims to analyze these two factors and their impact on TPACK among elementary school teachers. The study employed a quantitative correlational design; data were collected from 98 teachers through validated questionnaires on digital literacy, teacher motivation, and TPACK. Data were analyzed using descriptive and inferential statistics by linear regression analysis. The findings of this research lie in its exploration of the relationship between digital literacy, teacher motivation, and TPACK. It addresses a significant gap in the literature by examining the simultaneous interaction of these two variables on TPACK. The findings indicate a significant positive relationship between digital literacy and teacher motivation with TPACK, with correlation coefficients of 0.857 and 0.866, respectively. Digital literacy accounts for 73.5% of the variability in TPACK, while teacher motivation explains 75.1%. This study contributes to the existing literature by providing empirical evidence on the simultaneous effects of digital literacy and motivation on TPACK, a perspective often overlooked. Limitations include the study's focus on self-reported measures and a single geographic context, which may impact generalizability. The findings support the need for targeted professional development programs emphasizing both digital literacy and motivational strategies to enhance technology-based teaching in elementary education.